2015
DOI: 10.1002/clen.201300193
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Extraction of Flavonoids From Radix Scutellariae by Subcritical Water

Abstract: The extraction of baicalin, wogonoside, baicalein, and wogonin from Radix Scutellariae was performed using subcritical water and conventional extraction. Compared with ethanol extraction, subcritical water extraction required shorter extraction time, yielded a higher efficiency, and required less extraction solvent. The stability of four flavonoids under subcritical water conditions was investigated, and the extraction products can be controlled through adjusting the properties of subcritical water, namely the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It has been reported that subcritical water has a strong dissolving capacity for weakly polar compounds, including polycyclic aromatic hydrocarbons, fatty acids and biomasses . For example, subcritical water has been successfully applied to the extraction of phenols, flavonoids, alkaloids, essential oils, triterpenes, saccharides, organic acids and anthraquinones . With an increasing focus on green chemistry and natural drugs, subcritical water has gradually combined with other green additions, such as ethanol, ionic liquids, surfactants, carbon dioxide and enzymes .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that subcritical water has a strong dissolving capacity for weakly polar compounds, including polycyclic aromatic hydrocarbons, fatty acids and biomasses . For example, subcritical water has been successfully applied to the extraction of phenols, flavonoids, alkaloids, essential oils, triterpenes, saccharides, organic acids and anthraquinones . With an increasing focus on green chemistry and natural drugs, subcritical water has gradually combined with other green additions, such as ethanol, ionic liquids, surfactants, carbon dioxide and enzymes .…”
Section: Introductionmentioning
confidence: 99%